Trading volume - Stock return relationship: Evidence from the Baltic markets - Nguyen, Thi Mai Trang (My University, 2015)
This paper utilizes linear regression model and Granger causality test to examine the relationship between trading volume and stock returns in three Baltic markets: Estonia, Latvia and Lithuania. Daily index value of three types of indexes: OMX Tallinn, OMX Riga and OMX Vilnius present for three Baltic markets: Estonia, Latvia and Lithuania respectively. Trading volume correspondingly is taken from Baltic main and secondary lists. The research is made for a long period, from 2000 to 2015. Due to the financial crisis around 2007 the whole period is divided into two sub periods, pre-crisis (2000M1 – 2008M12) and post-crisis (2009M1 – 2015M2). Purpose of the study is to find out if there are any positive correlations between rate of returns and trading volume in any of these three markets. Moreover, the thesis employs Granger causality to investigate the causal relationship between trading volume and returns. Evidence from empirical research confirms that there are no positive relations between trading volume and returns in any of three markets in both two periods. No statistically significant relationship between trading volume and returns are found in general in Baltic market. In addition, no causal relationships are found in the first period. However, in the second period, trading volume Granger causes rate of return at 5% statistically significant in Latvia and Lithuania.
Keywords: trading volume; linear regression; Granger causality; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|